2017
DOI: 10.11138/mltj/2017.7.1.019
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic trans-osseous rotator cuff repair

Abstract: SummaryBackground: Mechanical factors are at the basis of any tendon healing process, being pressure an aspect able to positively influence it. For this reason transosseous rotator cuff repair represents the gold standard procedure for patients affected by a cuff tear, maximizing the tendon footprint contact area and reducing motion at the tendon to bone interface. Methods: The Authors present an all arthroscopic suture bridge-like transosseous repair with the preparation of a single transosseous tunnel perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 25 publications
0
8
0
2
Order By: Relevance
“…Another option to prevent such injuries, as an alternative to the technique of drilling straight tunnels, is to use one of the proprietary devices, such as the Arthrotunneler system (Wright Medical Group) or the Compasso device (NCS Lab), which help create an acute angled tunnel with a vertical limb and a horizontal limb. 4,7,10,18 This results in a tunnel that exits relatively proximal on the lateral aspect of the humerus, along with a thicker bone roof (a deeper tunnel). However, suture cutout through the bone tunnel has been reported even with these devices, with rates as high as 44%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another option to prevent such injuries, as an alternative to the technique of drilling straight tunnels, is to use one of the proprietary devices, such as the Arthrotunneler system (Wright Medical Group) or the Compasso device (NCS Lab), which help create an acute angled tunnel with a vertical limb and a horizontal limb. 4,7,10,18 This results in a tunnel that exits relatively proximal on the lateral aspect of the humerus, along with a thicker bone roof (a deeper tunnel). However, suture cutout through the bone tunnel has been reported even with these devices, with rates as high as 44%.…”
Section: Discussionmentioning
confidence: 99%
“…13,21 Over the past few years, many authors have described slightly differing versions of arthroscopic transosseous rotator cuff repair (ATORCR). 2,7,8,13,14,16,21 This method theoretically represents the best of both worlds, having the advantage of a minimally invasive arthroscopic procedure with the strength and cost-effectiveness of transosseous fixation.…”
mentioning
confidence: 99%
“…Since April 2015, we have used PGA threads for mattress sutures to gain the initial cuff securing force and avoid excessive tension on the rotator cuff. In addition to our method, other methods for arthroscopic transosseous repair of the rotator cuff without implant using an ArthroTunneler [5][6][7][8][9][10] , hollow needle [11][12][13] , special equipment [14][15] , and anterior cruciate ligament guide [16] have been reported. However, there have been on 4 reports describing clinical outcomes from arthroscopic transosseous repair of the rotator cuff without implant in more than 50 patients [1,10,11,13] .…”
Section: Discussionmentioning
confidence: 99%
“…All 6 stitches were then passed through the cuff to obtain the "2MC" (or "double MC") configuration with the tape ends passed more anteriorly and posteriorly. 13 Schematically, we refer to limb 1 as the most anterior and to limb 6 as the most posterior. We first closed limb 2 with limb 3 (suture 1) and later closed limb 4 with limb 5 (suture 2), leaving limbs 1 and 6 free.…”
Section: Surgical Techniquementioning
confidence: 99%
“…9 In an attempt to overcome the limitations of anchor repair, arthroscopic transosseous (TO) RC repair techniques have been developed. [10][11][12] In case of bone deficiency of the greater tuberosity, it is possible to use a lateral cortical augmentation device that is able to protect and reinforce the bone itself, 13 without any need to medialize the tendon insertion. 14 Several studies have shown that TO tunnels provide an excellent hold.…”
mentioning
confidence: 99%